A Review on Word Learning: Compilation of Theories and Experiments Advances - Gnyawali, Dipika; Panchakshari, Abhishek Budiguppe (Gipan, 2025)
Language learners and users regularly engages in a word-learning experience, demonstrating its huge prevalence. Activation of multiple brain areas, construction of multivariate linkages between mental sub-processes, and, control over numerous external and internal factors are essential for learning a single word, indicating the complex nature of word learning. However, such variables and processes involved in word learning have not received as much attention as required. Words are often perceived as a small element of language and implied as language semantics, so word investigations get overshadowed by language research. The only association of words with semantics has obscured the importance of phonological skills in word learning which needs to be highlighted more. Furthermore, word-related notions and studies are dispersed among linguists, psychologists, and speech pathologists, making it challenging for a new viewer to comprehend the precise nature of word learning because of the insufficient information compilation. The current article gathers data on word learning from different sources, reviewing experimental methodologies and theoretical studies on words from earlier to contemporary investigations. The article also delves deep into understanding the unique individualistic differences and variables influencing word learning. Henceforth, the article presents a theoretical summary and consists of experimental research, showcasing the breadth of word learning for an interested novice learner to apprehend.